PROGRAM PEMBERDAYAAN ANGGOTA SEBAGAI MODERASI KINERJA KEUANGAN ( PEARLS) PADA KESEJAHTERAAN ANGGOTA CREDIT UNION DI JAWA TIMUR - nekhasius agus sunarjanto (Media Mahardhika, 2022)
This research is on savings and loan cooperatives (Credit Union) with a research sample of credit cooperatives in East Java. The purpose of this research is to find out whether the empowerment program moderates financial performance on members' welfare. The results of the research explain that financial performance affects the member empowerment program by 82.19%. The significance of 0.011 , this shows that the empowerment of credit cooperative members (CU) is influenced by financial performance (PEARLS) and that the empowerment program has a positive effect on the welfare of members by 34% with a significance level of 0.02. This shows that the member empowerment program has a significant effect on the welfare of credit cooperative (CU) members.